Is news consumption related to abortion attitudes? An exploratory study with a nationally representative sample of US adults - Mena-Meléndez, Lucrecia; Crawford, Brandon L.; Valdez, Danny; LaRoche, Kathryn J.; Turner, Ronna C.; Jozkowski, Kristen N. (Frontiers in Communication, 2024)
The news is an efficient way to share information and plays an important role in shaping and reflecting cultural values and norms. However, research examining news consumption and abortion attitudes is limited. In this exploratory study, we analyzed data from a nationally representative sample of 886 US adults to assess whether self-reported frequency of news consumption-by news format (e.g., television, radio, newspaper, social media), news leaning (i.e., liberal, neutral, conservative), and total sum (i.e., total amount of consumption across leanings)-predicted abortion attitudes and complexity in attitudes. We conducted Poisson and negative binomial regression analyses controlling for demographic variables. We found that gender, political affiliation, Bible literalism, educational attainment, and abortion identity were significant predictors. While we did not observe a relationship between news format and abortion attitudes, we did find that the associations between news leaning and the total sum of news consumed varied across abortion identity. Our findings suggest that attitudes toward abortion may be differentially influenced by partisan news across abortion identity. After Dobbs v. Jackson, there is a need for advocates to tailor strategies to different sub-groups, promote media literacy, and encourage the use of diverse and balanced news sources to foster more informed views on abortion.